(untitled) (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: A popliteal cyst, also called a Baker cyst, is a benign uncontrolled swelling of the gluteus medius sac in the popliteal fossa at the back of the knee described this excess fluid and subsequent sac formation outside of the kneecap in the commencement.A Baker's (popliteal) cyst is a swelling of the knee's gastrocnemius-semimembranous bursa, which connects to the back of the synovial membrane. It commonly presents as a painless swelling in the popliteal fossa. Adults almost always develop an edema as a result of pathological changes to the knee joint. Sometimes, the cyst enlarges to the position in which it ruptures, releasing synovial fluid into the surrounding tissues and present physiologically as acute thrombophlebitis. Popliteal cyst infection is a rare complication that is often related to septic arthritis. Popliteal joint cysts, also known to as Baker's cysts, are sporadically together with intra-articular knee conditions like osteoarthritis and dislocated patella. Anatomically, the borders of the cyst resemble synovial tissue, and there may be chronic, non-specific inflammation. Even if they are not visible in the knee joint, osteocartilaginous loose bodies may be present within the cyst.CLINICAL FINDING: Pain in the back of knee were the main complaints of a 48-year-old female admitted to Tertiary Rural Hospital.DIAGNOSTIC EVALUATION: Chest x-ray and blood test including all tests are done. Were all performed as part of the physical evaluation to prevent acute and chronic post-surgical discomfort following Excision of Bakers cyst.THERAPEUTIC INTERVENTION: Post operative treatment advised 6 hours iv fluids normal saline, ringer lactate 500ml, antacids, antiemetic, analgesic given frequently advised as the first line of treatment following excision of baker cyst . It gives superior pain relief and allows for a speedier recovery.OUTCOMES: Patient condition was poor.CONCLUSION: Baker cyst is a benign uncontrolled enlargement of the bursa in the popliteal fossa at the back of the knee that is diagnosed in the hospital on the IPD based on the patient having symptoms of swelling and pain in the back of knee. Based on a patient admitted to Tertiary Rural Hospital for diagnostic tests are done as per doctor order blood test, surgery of the excision of cyst . To reduce acute and chronic post-surgical pain after excision baker cyst. Post operative medications advised.